Radon-222 indoor and association with lung cancer risk in the Metropolitan Region of Recife, Brazil (Revista Brasileira Multidisciplinar, 2023)
Radon-222 is a noble gas considered a Class 1 human carcinogen known as the second cause of lung cancer after smoking. Formed from uranium-238 present in uranium phosphorite which, when exhaled into the atmosphere, can accumulate indoors, posing a risk to human health. This study has the objective of analyze the risk of lung cancer associated with radon-222 in areas of uranium occurrence located in the Metropolitan Region of Recife, PE, Brazil. The monitoring of gas in the atmosphere of residences was carried out by exposing CR-39 detectors in diffusion chambers. The indoor radon concentrations found in the studied residences ranged from 2 to 1174 Bq m-3, being mostly higher than the values recommended by the World Health Organization and the European Union. It can be inferred that this study at the local level contributes to national estimates of lung cancer incidence, prioritizing health protection in inhabited areas with uraniferous occurrence.
Keywords: Lung cancer; Radon; Radioprotection; Health